2021
DOI: 10.1155/2021/5516521
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial-Derived Mesenchymal Stem Cells: Characteristics and Progress in Tissue Regeneration

Abstract: Maxillofacial-derived mesenchymal stem cells (MFSCs) are a particular collective type of mesenchymal stem cells (MSCs) that originate from the hard and soft tissue of the maxillofacial region. Recently, many types of MFSCs have been isolated and characterized. MFSCs have the common characteristics of being extremely accessible and amazingly multipotent and thus have become a promising stem cell resource in tissue regeneration. However, different MFSCs can give rise to different cell lineages, have different ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 206 publications
(364 reference statements)
0
5
0
Order By: Relevance
“…The field of regenerative medicine has increasingly recognized MSCs due to their convenient procurement, in vitro self-renewal, multidirectional differentiation, and migration potential [ 6 , 7 ]. Notably, MSCs exhibit attributes characterized by anti-inflammatory and immunomodulatory properties, fostering tissue and organ regeneration, which play an indispensable role in various inflammatory and autoimmune diseases [ [8] , [9] , [10] ].…”
Section: Mscsmentioning
confidence: 99%
“…The field of regenerative medicine has increasingly recognized MSCs due to their convenient procurement, in vitro self-renewal, multidirectional differentiation, and migration potential [ 6 , 7 ]. Notably, MSCs exhibit attributes characterized by anti-inflammatory and immunomodulatory properties, fostering tissue and organ regeneration, which play an indispensable role in various inflammatory and autoimmune diseases [ [8] , [9] , [10] ].…”
Section: Mscsmentioning
confidence: 99%
“…Maxillofacial-derived MSCs (MFSCs) have caught scientists’ attention due to their multipotentiality and easy accessibility. These stem cells have shown promise in teeth, periodontal tissue, and bone regeneration, as well as helping in wound healing (Yan et al 2021). However, the efficacy of MFSCs in clinical treatment is not as effective as the biological model, most likely due to the complex and dynamic oral microenvironment.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In addition to these well-studied populations, maxillofacial-derived MSCs (dental pulp stem cells, etc.) are favored in basic and clinical research due to their extreme ease of accessibility (Liu et al 2015; Yan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Current identified DSCs are dental pulp stem cells (DPSCs) (1,2), stem cells from human exfoliated deciduous teeth (SHED) (3), periodontal ligament stem cells (PDLSCs) (4), dental follicle precursor cells (DFPCs) (5), stem cells from apical papilla (SCAP) (6), gingival-derived MSCs (GMSCs) (7), and alveolar bone marrow-derived MSCs (ABMSCs) (8,9). In vitro identification demonstrated that DSCs positively expressed MSC-related markers, including CD13, CD29, CD44, CD59, CD73, CD90, CD105, CD146, and STRO-1; while negatively expressed hematopoietic markers, such as CD14, CD31, CD34, and CD45 (10)(11)(12). The key pluripotency markers (Oct4, Sox2, and Nanog) that are involved in maintaining the undifferentiated state were also expressed in DSCs with different levels (13).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has indicated that DSC fate is of great importance in directing their functions (11,24). Potentiated to osteogenesis, adipogenesis, chondrogenesis, neurogenesis, and angiogenesis, DSCs may facilitate multiple tissue regeneration (25).…”
Section: Introductionmentioning
confidence: 99%